2017
DOI: 10.3892/mmr.2017.7300
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+/Mg2+ homeostasis-related TRPM7 channel mediates chondrocyte hypertrophy via regulation of the PI3K-Akt signaling pathway

Abstract: Chondrocytes are specialized cells that form cartilage tissue, and are able to respond to their osmotic environment and exercise important roles in endochondral ossification via undergoing proliferation, hypertrophy and apoptosis. The transient receptor melastatin potential 7 (TRPM7) cation channel can modulate the intracellular and extracellular levels of Ca2+ and Mg2+, and therefore the cellular osmotic environment. However, the molecular pathways involved in TRPM7‑mediated signal transduction have yet to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 23 publications
4
15
0
Order By: Relevance
“…6 and 8). Our conclusion is in accordance with a report that TRPM7 channels are involved in hypertrophic differentiation of cultured chondrogenic ATDC5 cells in vitro (13) and is further supported by the observation that bone outgrowth is systemically perturbed in zebrafish bearing a Trpm7 mutation (9). The bone phenotypes in this mutant zebrafish are consistent with the histological and cytological defects associated with the reduced bone outgrowth that we observed in cultured Trpm7-deficient metatarsals and in femurs from chondrocyte-specific Trpm7 knockout mice.…”
Section: Discussionsupporting
confidence: 93%
“…6 and 8). Our conclusion is in accordance with a report that TRPM7 channels are involved in hypertrophic differentiation of cultured chondrogenic ATDC5 cells in vitro (13) and is further supported by the observation that bone outgrowth is systemically perturbed in zebrafish bearing a Trpm7 mutation (9). The bone phenotypes in this mutant zebrafish are consistent with the histological and cytological defects associated with the reduced bone outgrowth that we observed in cultured Trpm7-deficient metatarsals and in femurs from chondrocyte-specific Trpm7 knockout mice.…”
Section: Discussionsupporting
confidence: 93%
“…It has been previously shown that Mg 2+ treatment could increase intracellular Mg 2+ concentrations and activate Akt phosphorylation [42], whereas decrease of intracellular Mg 2+ was observed during the mitochondrial apoptosis of colon cancer cells [43]. Mg 2+ was a necessary factor for stabilisation of the mitochondrial membrane [44], possibly due to the maintenance of intracellular Mg 2+ /calcium (Ca 2+ ) homeostasis [45]. Indeed, a previous study showed that Mg 2+ could inhibit the uptake of Ca 2+ by mitochondria, which was the initiating factor of MMP loss and Cytochrome C release [46].…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/AKT pathway is also affected by TRPM7. In mouse chondrocytes, overexpression of TRPM7 stimulated the AKT pathway, while TRPM7 silencing inhibited AKT signaling [136]. In human osteoblasts, Mg 2+ -induced increase in mRNA expression of chemotaxis-related genes was attenuated by TRPM7 siRNA and PI3K inhibition, suggesting a link between TRPM7 and PI3K activation mediated by Mg 2+ .…”
Section: Cross-talk Between Trpm6/7 Receptor Tyrosine Kinases Andmentioning
confidence: 99%